Tissue- and sex-specific lipidomic analysis of Schistosoma mansoni using high-resolution atmospheric pressure scanning microprobe matrix-assisted laser desorption/ionization mass spectrometry imaging. - Patrik Kadesch; Thomas Quack; Stefanie Gerbig; Christoph G Grevelding; Bernhard Spengler (Public Library of Science (PLoS), 2020)
Schistosomes are human pathogens causing the neglected tropical disease schistosomiasis, which occurs worldwide in (sub-)tropical regions. This infectious disease is often associated with poverty, and more than 700 million people are at risk of infection. Exploitation of novel habitats and limited therapeutic options brought schistosomes into research focus. Schistosomes are the only trematodes that have evolved separate sexes. They are covered by their metabolically active tegument, a surface area representing the interface between male and female in their permanent mating contact but also between parasite and host. The tegument comprises, besides others, numerous specific lipid compounds. Limited information is available on the exact lipid composition and its spatial distribution. We used atmospheric-pressure scanning microprobe matrix-assisted laser desorption/ionization (AP-SMALDI) mass spectrometry imaging (MSI) to characterize the Schistosoma mansoni tegument surface in comparison to tissue sections of whole worms or couples. We found that phosphatidylcholines (PC) and specific phosphatidylethanolamines (PE) are significantly more abundant inside the worm body compared to the tegument. On the other hand, the latter was found to be enriched in sphingomyelins (SM), phosphatidylserines (PS), lysophosphatidylcholines (LPC), and specific PE species. We further investigated lipid classes concerning number of carbon atoms in fatty acyl chains as well as the degree of unsaturation and found pronounced differences between the tegument and whole-worm body. Furthermore, differences between male and female teguments were found. The lipid composition of S. mansoni tissues has been investigated in an untargeted, spatially resolved manner for the first time.